The impact of changing working patterns for police personnel in England and Wales during Covid-19 lockdown 1 - Fleming, Jenny (Routledge international handbook of policing crises and emergencies, 2025)
A national health emergency, coupled with public order and restraint imperatives, compounded the levels of stress in policing. In England and Wales, new working patterns were negotiated to manage the constraints of a different working environment during the Covid-19 pandemic. This chapter explores the impacts of the Covid lockdown restrictions on police personnel in lockdown 1, utilising five themes: preparedness and protection, relationships with the public, changing work demands, communication, and support. Empirical data comprising the qualitative comments of frontline police personnel derived from a broader online national survey are reported to illustrate sentiment towards these issues. The qualitative data suggests that frustration and disappointment, combined with changing work practices and a perceived disconnection with the public, heightened stress levels in those working on the front line during lockdown 1.